Polyheterocycles containing alkene spacer linkages Part I. Synthesis and electropolymerization of 3-styrylthiophenes - Smith, J.R.; Campbell, S.A.; Ratcliffe, N.M.; Dunleavy, M. (Synthetic metals, 1994)
The synthesis and electrochemical behaviour of novel thiophene compounds containing a substituted phenyl group separated by an alkene spacer are described. In such systems, it was proposed that the molecular geometry should allow the π-electron density of the phenyl group to be delocalized with that of the thiophene ring by means of the alkene spacer. The presence of this unsaturated linkage should also minimize steric hindrance between the two rings. A number of such monomers exhibiting a range of electronic effects were prepared and their electrochemical behaviour investigated. Although films were deposited on the anode surface by electropolymerization, the conductivities were of the order of 10 −6 S cm −1. The nature of the films was investigated by electrochemical and microscopic techniques. Potentiodynamic studies indicated that the alkene spacer linkage may be subject to irreversible electrooxidation. Polymer redox peaks, characteristic of anion mobility within conductive polymers, were absent from the cyclic voltammograms. SEM observations showed that the films were exceptionally smooth and homogeneous.